Value assessment of medicinal products by the Italian Medicines Agency (AIFA) and French National Authority for Health (HAS): Similarities and discrepancies - Xoxi, Entela; Di Bidino, Rossella; Leone, Serena; Aiello, Andrea; Prada, Mariangela (Frontiers in Medical Technology, 2022)
The evaluation of pharmaceutical innovation and therapeutic value is an increasingly complex exercise for which different approaches are adopted at national level, despite the need for standardisation of processes and harmonisation of public health decisions. The objective of our retrospective analysis was to compare the approaches of AIFA (Agenzia Italiana del Farmaco) and HAS (Haute Autorité de Santé) in assessing the same medicinal products. In Italy, the 1525/2017 AIFA Deliberation introduces a transparent scheme for the evaluation of innovative status (innovative, conditional, not innovative) based on therapeutic added value (TAV), therapeutic need, and quality of evidence. By contrast, in France, HAS makes judgements using the effective clinical benefit (SMR) and improvement of effective clinical benefit (ASMR). The analysis focused on medicinal products evaluated both by AIFA and HAS from July 2017 to September 2021. Similarities between AIFA and HAS evaluations were investigated in terms of TAV, recognition of innovativeness and ASMR. Both total and partial agreement were considered relevant. Therefore, raw agreement, Cohen’s kappa (weighted and unweighted), and Bangdiwala’s B-statistic were estimated. A total of 102 medicinal products were included in this study. 38 (37.2%) were orphan drugs, while 56 (54.9%) had a clinical indication for the treatment of cancer. AIFA and HAS reached a higher agreement on the innovativeness status compared to TAV. A moderate total agreement emerged in the recognition of innovativeness (k =0.463, p-value ≤0.0001), and the partial agreement was substantial (equal weight k =0.547, squared k =0.638), while a lack of agreement resulted in the comparison of the TAV according to AIFA and the ASMR recognised by HAS. Indeed, whereas AIFA determined TAV to be important, HAS considered it to be moderate. In addition, whereas AIFA identified a bias towards moderate TAV, HAS identified a bias towards minor ASMR. A higher level of agreement was reached, both on TAV and innovative status, for less critical medical products (non-cancer related or non-orphan or with a standard EMA approval). These results underline the importance of implementing European procedures that are more broadly aligned in terms of value definition criteria.